On Syzygy Modules over Laurent Polynomial Rings - Morou Amidou; Ousmane Moussa Tessa (International Journal of Mathematics and Mathematical Sciences)
In this paper, we present a dynamical method for computing the syzygy module of multivariate Laurent polynomials with coefficients in a Dedekind ring (with zero divisors) by reducing the computation over Laurent polynomial rings to calculations over a polynomial ring via an appropriate isomorphism.